Social Dominance Orientation, Right‐Wing Authoritarianism, and Willingness to Carry out Three Domains of Socially Inclusive Behaviors in a Public Campaign. Issue 1 (10th April 2020) - Zhao, Kun; Faulkner, Nicholas; Perry, Ryan
Abstract: Ideological attitudes supporting group‐based dominance (i.e., social dominance orientation, SDO) and in‐group authority (i.e., right‐wing authoritarianism, RWA) are well‐established dual antecedents of prejudice. We extend classic perspectives of prejudice as an attitudinal outcome by testing this dual‐antecedent model with prejudice operationalized as inclusive behavioral intentions in a nationally‐representative Australian community sample (N = 2, 632). An exploratory structural equation model simultaneously derived three domains of behavioral intentions in the data: small, interpersonal gestures (e.g., saying hello to people from other groups), volunteering to help the disadvantaged (e.g., mentoring people from disadvantaged groups), and political action (e.g., organizing a demonstration). There was evidence for a dual‐motivational basis of inclusive behavior intentions, with SDO negatively predicting all three categories of behaviors, particularly interpersonal gestures, while RWA showed a small negative relation only with political action. The findings suggest that motivations for group‐based dominance are the primary barrier against behavioral intentions toward social inclusion, which can inform the design of public interventions for reducing prejudice and discrimination.